Evaluation of I-Kelahiran, A Health Informatics System in Sabah State Health Department – A Structural Equation Modeling - Cheah, Whye Lian; Dhesi Baha, Raja Selva Raja; Anselm, Su Ting ("Iuliu Haţieganu" Publishing House, 2020)
I-Kelahiran (Inovasi-Kelahiran) is a health informatics system that manages birth and immunisation data, developed and implemented in Sabah to address birth discrepancy, delayed reporting of high-risk pregnancy, and immunization coverage. This study aimed to evaluate the conceptual framework and the factors that determine the information system success of I-Kelahiran among the nurses in the Sabah State Health Department. It was a cross-sectional web-based study, conducted in 21 hospitals and 292 health clinics. A total of 1.200 nurses participated, with a mean age of 31.96 years (SD=7.761) and the majority of them were community nurses. About 93.8% of them had good computer literacy. Individual Impact (p=0.011) and Organizational Impact (p=0.0019) were seen to have significant association towards the nurse's place of work, and computer literacy had a significant association towards organizational impact (p=0.046). A structural equation modeling indicated that only perceived ease of use & importance of system are good predictors in outcome evaluation of I-Kelahiran while Individual Impact & Effectiveness are good domains to measure the overall outcome of I-Kelahiran (Chi-Square/df=2.850, Comparative Fit Index [CFI]= 0.991, Tucker-Lewis Index [TLI]= 0.989, Root Mean Square Error Of Approximation [RMSEA]= 0.939). Future study is needed to study the complex external factors that lead to this information success model in Malaysia